Circadian and seasonal variation in the essential oil from Virola surinamensis leaves - Lopes, N. P.; Kato, M. J.; Andrade, EHDA; Maia, JGS; Yoshida, M. (Elsevier B.V., 1997)
The essential oil from leaves of Virola surinamensis shows circadian variation in elemicin and in monoterpenes during the rainy season (February). The monoterpenes represents 50% of total volatile compounds during the dry season(June). Sesquiterpenes are predominant (50%) in the early rainy season (October). (C) 1997 Published by Elsevier B.V. Ltd.
Keywords: Virola surinamensis; Myristicaceae; essential oil; essential sesquiterpenes; elemicin; circadian variation; seasonal variation